2020
DOI: 10.3390/su12229619
|View full text |Cite
|
Sign up to set email alerts
|

Internet Access in Rural Areas: Brake or Stimulus as Post-Covid-19 Opportunity?

Abstract: The lack of internet access in most rural areas has become a challenge worldwide. The Covid-19 pandemic has highlighted trends such as teleworking and e-commerce, meaning an opportunity for the local economy of these areas, but with serious difficulties in carrying it out. This paper aims to detect this lack of internet in inland areas of the region of Valencia through local actors, in order to identify clear priorities and real needs through an explorative and replicable approach based on agglomerative hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…does not have a significant influence. The research results are in line with the results of other studies [61][62][63][64][65].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…does not have a significant influence. The research results are in line with the results of other studies [61][62][63][64][65].…”
Section: Resultssupporting
confidence: 91%
“…They concluded that education level, jobs requiring higher qualifications, age, gender, and living in rural or urban areas strongly influence teleworking. Ruiz-Martinez and Esparcia [64] also analyzed the impact of internet access on telework and e-commerce in rural areas of Spain and concluded that the lack of adequate infrastructure can adversely affect them, highlighting local the role of local authorities in ensuring sufficient infrastructure. Lewis [65] researched the impact of I.C.T.…”
Section: Discussionmentioning
confidence: 99%
“…Issa and Bergs ( 2022 ) use Sentinel 5P image composites showing NO 2 emissions (14 days moving averages of daily images from March to April 2020), local data on Covid-19 incidence, and the local level of teleworkability to estimate the potential reduction of greenhouse gas emissions in German regions exhibiting different economic structures. Using municipality-level data of de-population risk linked to a survey in the Valencia region (Spain) during the Covid-19 period, Ruiz-Martinez and Esparcia ( 2020 ) show how functions and economic prospects of rural regions depend on the local internet access.…”
Section: The Different Dimensions Of the Use Of Small-scale Spatial Datamentioning
confidence: 99%
“…La creciente brecha digital de muchas áreas rurales respecto de los centros urbanos constituye un factor de desequilibro que contrarresta esas ventajas, contribuyendo, por un lado, a frenar esa posible relocalización de profesionales más vinculados o próximos a las nuevas formas de trabajo deslocalizado; por otro, a frenar o limitar el atractivo en tanto que residencias secundarias o espacios de ocio para población urbana; y, finalmente, en cuanto se está convirtiendo en una brecha también social, en tanto que el acceso a servicios de internet suficientes son considerados como un derecho básico (tal como declaró la propia ONU en 2016). El trabajo de investigación puso de relieve tales deficiencias y, como consecuencia, la creación de nuevas redes de gobernanza y mecanismos de innovación (Ruiz-Martínez & Esparcia, 2020).…”
Section: Desarrollo Inteligenteunclassified